Frequency of Genitourinary Abnormalities in Patients Having Anorectal Anomalies - Din, Islam Ud; Khan, Muhammad Younas (Biological and Clinical Sciences Research Journal, 2025)
Anorectal malformations (ARMs) are frequently associated with genitourinary anomalies, which can lead to significant morbidity if left undiagnosed. Early detection is critical for optimal clinical management and prognosis. Objective: To determine the frequency and pattern of genitourinary abnormalities in neonates diagnosed with anorectal malformations. Methods: A descriptive cross-sectional study was conducted at the Department of Pediatric Surgery, Lady Reading Hospital, Peshawar, Pakistan, from 05-07-2024 to 05-01-2025. One hundred fifty-one neonates aged 1–30 days with radiologically confirmed ARMs were enrolled through non-probability consecutive sampling. Neonates with prior surgical interventions or genital ambiguity were excluded. Data on demographic variables and ARM type (high vs. low lesion) were collected. Genitourinary anomalies were identified through clinical examination, ultrasound, voiding cystourethrogram (VCUG), and intravenous pyelography. Statistical analysis was performed using SPSS version 25, and p-values <0.05 were considered significant. Results: Out of 151 neonates, 89 (58.9%) were male and 62 (41.1%) were female. Genitourinary anomalies were present in a substantial proportion of patients. The most common abnormality was vesicoureteral reflux (VUR), found in 52 cases (34.4%), followed by hypospadias in 19 cases (12.6%), ureteropelvic junction obstruction (UPJO) in 18 cases (11.9%), and undescended testis (UDT) in 8 cases (5.3%). Hypospadias and UDT were exclusively observed in male neonates (p < 0.001). High-type ARMs (n=63, 41.7%) were significantly associated with increased genitourinary anomaly frequency. Conclusion: Genitourinary anomalies, particularly vesicoureteral reflux, are common in neonates with anorectal malformations, especially those with high-type lesions. Routine screening with ultrasound and VCUG is essential to identify and manage these associated abnormalities early, thereby improving long-term outcomes.